Teori Komunikasi Perspektif Indonesia: Gagasan dan Kemungkinan - Abdul Hair (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2020)
This article discusses the possibility of initiating the Indonesian perspective of communication theory, an idea that was derived, while also drawing inspiration, from the Asian perspective of communication theory offered by Kincaid and Dissanayake in the 1980s. The question raised in this article is, is it still relevant to formulate a communication theory based on Indonesian culture, as globalization has increasingly blurred the boundaries between "the local" and "the global"? By using cultural studies and postcolonial theories, as well as literature study methods, the results show that it is possible to initiate communication theory from the Indonesian perspective, although this possibility is still accompanied by a few notes. First and foremost, problematizing the concept of Indonesia itself. Second, conducting dialogue with other scientific disciplines which also criticize the hegemony of Western theories. By adhering to the two notes above, the Indonesian perspective of communication theory is expected to avoid the trap of essentialism and ahistoricism, as seen in various other approaches that also criticize the hegemony of Western theories in communication studies.